Base excess as a prognostic factor determining the perinatal outcome - P., Chandrakala; Lysander, Shilpa Deborah; ., Jayalalitha (International Journal of Contemporary Pediatrics, 2020)
Background: Umbilical cord blood gas assessment seems to be the most objective determination of fetal metabolic condition at the time of birth and can be used to assess the perinatal outcome of the baby. In the early stage of an impaired placental circulation, hypoxemia and hypercapnia result in a decrease in pH with BD maintained normal (respiratory acidemia), whereas if the hypoxic process develops into a sustained anaerobic metabolism the BD rises secondary to lactic acidosis and consumption of buffer. Methods: Observational study done in KIMS hospital Bangalore, Karnataka, India, in a study period of 18 months on a sample size of 100. Within 30 sec of delivery a segment of umbilical cord was clamped at both ends. Cord blood was collected in heparinised syringe. It was then transported with cold ice packs and blood pH, pCO2, pO2 were measured. Results: In present study, there was a significant difference between the 2 groups in terms of BE, BE being highest in the group without complication. There was a moderate negative correlation between duration of NICU stay (days) and BE (mmol/L), and this correlation was statistically significant. There was a significant difference between the 2 groups in terms of BE with the median BE (mmol/L) being highest in the group not requiring resuscitation. At a cutoff of BE (mmol/L) <-17.5, it predicts complications with a sensitivity of 71.4%, and a specificity of 88.2%. Conclusions: Hence cord blood base excess can be used as a prognostic factor in determining the perinatal outcome.